2015
DOI: 10.1093/mnras/stv180
|View full text |Cite
|
Sign up to set email alerts
|

The density structure and star formation rate of non-isothermal polytropic turbulence

Abstract: The interstellar medium of galaxies is governed by supersonic turbulence, which likely controls the star formation rate (SFR) and the initial mass function (IMF). Interstellar turbulence is non-universal, with a wide range of Mach numbers, magnetic fields strengths, and driving mechanisms. Although some of these parameters were explored, most previous works assumed that the gas is isothermal. However, we know that cold molecular clouds form out of the warm atomic medium, with the gas passing through chemical a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
129
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(144 citation statements)
references
References 135 publications
(221 reference statements)
14
129
1
Order By: Relevance
“…Overall, model predictions seem to match with numerical results up to numerical uncertainties, although more detailed comparisons will be necessary to understand its successes and failures more completely. We finish with an extension to non-isothermal turbulence (illustrating reasonable qualitative agreement with the simulations of Federrath & Banerjee 2015) and a discussion of MHD, before concluding by reiterating the model's main predictions.…”
Section: Introductionmentioning
confidence: 56%
See 2 more Smart Citations
“…Overall, model predictions seem to match with numerical results up to numerical uncertainties, although more detailed comparisons will be necessary to understand its successes and failures more completely. We finish with an extension to non-isothermal turbulence (illustrating reasonable qualitative agreement with the simulations of Federrath & Banerjee 2015) and a discussion of MHD, before concluding by reiterating the model's main predictions.…”
Section: Introductionmentioning
confidence: 56%
“…(iv) The assumption that the shock width is equal to the sonic scale-while useful as a phenomenological tool for deriving density variance-Mach number relations (Price et al 2011;Padoan & Nordlund 2011;Molina et al 2012;Federrath & Banerjee 2015)is inconsistent with log-normal density statistics. In particular, for isothermal shocks with a density contrast ∼ M 2 , such a model involves all of the mass being concentrated in a single shock, which leads to an unphysically intermittent density distribution.…”
Section: General Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is supersonic, magnetized turbulence that determines the density PDF and, in particular, its standard deviation (Padoan et al 1997b;Federrath et al 2008b;Padoan & Nordlund 2011;Price et al 2011;Konstandin et al 2012;Burkhart & Lazarian 2012;Molina et al 2012;Federrath & Banerjee 2015;Nolan et al 2015). A high-density power-law tail can develop as a consequence of gravitational contraction of the dense cores in a cloud (Klessen 2000;Federrath et al 2008aFederrath et al , 2011bKritsuk et al 2011;Federrath & Klessen 2013;Girichidis et al 2014).…”
Section: Density Pdf and Conversion From Twomentioning
confidence: 99%
“…6. THE EFFECTIVE TURBULENT DRIVING Theoretical and numerical studies have shown that the density fluctuations (s r r 0 ) in a turbulent medium correlate with the Mach number () and the driving of the turbulence, which is controlled by the turbulence driving parameter b (Federrath et al 2008bPrice et al 2011;Konstandin et al 2012;Federrath & Banerjee 2015;Nolan et al 2015), . While Equation (8) lists the three special cases (solenoidal, mixed, compressive), the driving parameter can vary continuously in the range   b 1 3…”
Section: The Sonic Scale and Filament Widthmentioning
confidence: 99%